THE TERMS OF ACQUIRING EIGENDOM RIGHT ON LAND THROUGH STATUTE OF LIMITATION (DALUWARSA) - Hartini Atikasari (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
This paper contains about how to apply the law of transfer of right on land as well as the requirements for acquiring eigendom right on land through statute of limitation(daluwarsa), both before the enactment of the Law Number 5 of 1960 concerning Basic Agrarian Law (hereinafter referred as BAL) and after the enactment of the BAL. Furthermore, the prerequisites for obtaining eigendom right on land will be analysed based on the provisions of the principle of good faith, also describe the reasons for property rights to be nullified and become state land according to the applicable law. There is also in this paper the author uses normative legal research methods by utilizing legal literatures and legal dictionaries. This research resulted in unexpected conclusions because based on literature studies, legal facts were produced if there were differences in the rules for acquiring land right through statute of limitation between the Civil Code and the BAL, so that it had implications for the land law system in Indonesia.